Development of a mobile training app to assist radiographers' diagnostic assessments. (10th June 2022) - Toderis, Liat; Vo, Ace; Reychav, Iris; Sayeed, Lutfus; McHaney, Roger; Guindy, Michal
The current study reduced the time lag between performing a diagnostic assessment and identifying a critical finding in CT and MRI exams through improving radiographers' abilities to identify those critical findings. Radiographers' diagnostic assessments in CT and MRI exams were used to develop a mobile training application with the aim to improve radiographers' awareness of critical findings. The current research used data analytics to examine radiographers' interpretation of imaging studies from a privately owned medical group in Israel. During the project, the radiographers' ability to identify critical findings improved. Implementation of the mobile training program yielded positive results where the knowledge gap was reduced and time to identify critical cases was decreased. Specifically, this study showed that radiographers can be trained in ways that enhance their involvement with radiologists to provide high quality services and improve treatment Ultimately, this gives patients higher quality of care and safer treatment.